A Linguistic Understanding of the Poetic Travelogue Niraat London: A Reflection of Language Use and Change - Chokthawikit, Sirisira (Journal of the Faculty of Arts, Silpakorn University, 2020)
This article focuses on the relationship between language and the meaning of Niraat London, which was characterized and structured according to the era. Linguistic changes at the levels of morphology, word use and syntax in Niraat London are challenging to read and interpret for those who use current principles of analysis to analyze past texts without reviewing the issue of language use in different periods. This defect is resolved by incorporating the concept of historical linguistics into consideration. Eventually, it has become interdisciplinary in the academic and research world, which is so-called literary linguistics. Although the use of linguistics in this research is employed, the sequences of ideas are presented as a literary study in order to access the coordination between disciplines, and explain each phenomenon by means of descriptive analysis, and conceptual argument. The findings are two outcomes namely 1) language characteristics such as word use and meaning including some changeable grammatical structures, and 2) story/content characteristics with reflections of thought and practice with regard to language use. Both language and content dimensions are the convergence of linguistic changes and modes of representation through Niraat London.